(3cJGHI Chd HMK , eQGMd cJGHI GdHMK GdYdej,GdETQGa h GdefGbTIs - (3ScjfI(B, (3Hf MehOs ((3GdLRGFQ(B:s (3JOjcdJ(B,s, 2019)
(3GdefgLjI h GdHMK GdYdej , cja JcJH HMKG dChd eQI aj GdYdhe GdGbJUGOjI , efGgL GdHMK GdYdej , eQGMd cJGHI GdHMK GdYdej , GdGTQGa Ydi HMhK GdeGSJQ h GdeGLSJjQ h GdOcJhQGgh CNjQG efGbTI HMhK GdeGSJQ h GdeGLSJjQ h GdOcJhQGg(B.s
(3eQGLY U(B.186s
Keywords: (3GdHMK GdYdejs; (3GdefgLjIs